KARAKTERISTIK SITIRAN ARTIKEL ILMIAH TENTANG KAJIAN MINANGKABAU DALAM JURNAL â€œSULUAHâ€ TAHUN 2001-2012 TERBITAN BALAI PELESTARIAN SEJARAH DAN NILAI TRADISIONAL (BPSNT) PADANG - Emidar, Emidar; Rahmah, Elva; Nelisa, Malta (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2015)
This study aims to describe: (1) writersâ€™ quotation in Jurnal â€œSuluahâ€ published by Balai Pelestarian Sejarah dan Nilai Tradisional Padang, (2) characteristics of literatures quoted by writers, and (3) authorship pattern. Quotation analysis method is used to study the relation between quoting documents and the documents quoted. The object of this study is the publications in Jurnal Suluah in 2001-2-12.The research finds that: (1) writersâ€™ quotation pattern based on article contribution and the number of quotations in articles is 155 articles and 1607 quotations. In average, one article quotes ten documents from various forms of sources. (2) Characteristics of literatures quoted by writers based on genre, year, and age of literatures are as follows: (a) the most contributing document in article writing is book, achieving 1316 quotations; (b) the year span of documents quoted is from 1827 to 2010; and (c) the age of the most cited documents is those published in the last ten years (2001-2010) as much as 35%; (c) the pattern of authorship is that the most cited writer is Koentjaraningrat with 37 citations. The rate of collaborations of the author is very low, because 97% of articles are written by a single author and only 3% are multiple authors.Keywords: scientific articles quotation, Minangkabau study, Jurnal Suluah